Effect of diethyl ether additive in Jatropha biodiesel‐diesel fuel blends on the variable compression ratio diesel engine performance and emissions characteristics at different loads and compression ratios. Issue 8 (30th June 2020) - Varpe, Bahusaheb R.; Kharde, Yashwant R.; Rahman, Kalyandurg Fazlur; Khidmatgar, Abdulqhadar
Abstract: An investigational analysis was performed to assess the effect of diethyl ether (DEE) that acts as an oxygenated additive in Jatropha biodiesel and diesel fuel blends on the performance enhancement and emission reduction of a variable compression ratio (CR) diesel engine. The DEE (10% vol) is added to different concentration levels of Jatropha biodiesel (B5, B10, and B20). The Jatropha biodiesel (JME) is prepared by the transesterification reaction and DEE is prepared through acid distillation of ethanol. The various tests were conducted by varying the loads at 25%, 50%, 75%, and 100% (3, 6, 9, and 12 kg). The DEE was entirely miscible with diesel and Jatropha biodiesel, the addition of DEE increases the cetane and calorific value, kinematic viscosity of the fuel blends compared with neat diesel or Jatropha biodiesel. The results illustrate that at higher loads and CRs, the engine performance parameters such as brake thermal efficiency enhances and reduces the brake‐specific fuel consumption for DEE‐Jatropha biodiesel‐diesel fuel blends. Blend A3 (10% DEE + 20% JME + 70% diesel) demonstrated an overall improvement in the engine performance parameters and emission characteristics compared with A1, A2, and diesel fuel blends. It is concluded that the DEE‐JME‐diesel fuel blend is a promising source of fuel for diesel engine at maximum load.